Exercise-Induced Neuroprotection and Recovery of Motor Function in Animal Models of Parkinson's Disease - Palasz, Ewelina; Niewiadomski, Wiktor; Gasiorowska, Anna; Wysocka, Adrianna; Stepniewska, Anna; Niewiadomska, Grazyna (Frontiers in Neurology, 2019)
Parkinson’s disease (PD) is manifested by progressive motor, autonomic and cognitive disturbances. Dopamine (DA) synthesizing neurons in the substantia nigra (SN) degenerate causing a decline in DA level in striatum leading to characteristic movement disorders. Loss of DA neurons in the ventral tegmental area (VTA) may be connected with non-motor disturbances. Disease-modifying therapy to arrest PD progression remains unattainable with current pharmacotherapies, most of which cause severe side effects and with time lose their efficacy. For this reason, there is a need to seek new therapies supporting the pharmacological treatment of PD. In pharmacologically treated PD patients motor therapy is recommended as it alleviates symptoms. Motor therapy applied in established PD still improves some motor functions. However, the mechanisms of motor therapy effects are unknown, it is also not known whether motor therapy may be neuroprotective in PD patients. Due to obvious limitations, human studies are unlikely to answer these questions, therefore, the use of animal models of PD seems indispensable. Motor therapy in animal models of PD characterized by the loss of dopaminergic neurons has neuroprotective and neuroregenerative effects, and nearly complete neuronal protection may be achieved unless i) neuronal loss is too extensive, ii) duration of exercise is too short, or iii) its initiation commences too late post-insult. As the physical activity is neuroprotective for dopaminergic neurons, the question arises what is the mechanism of this process. A hypothesis assumes the central role of neurotrophic factors in the neuroprotection of dopaminergic neurons induced by physical activity, while it is still not clear whether increased DA level in nigrostriatal axis results from the neurogenesis of dopaminergic neurons in the SN, recovery of phenotype of dopaminergic neurons, increased sprouting of the residual dopaminergic axons in the striatum or generation of local striatal neurons from inhibitory interneurons. In the present review, we discuss studies describing the influence of physical exercise on the PD-like changes manifested in animal models of the disease and focus our interest on the current state of knowledge on the mechanism of neuroprotective properties of physical activity as supportive therapy in PD.